2020
DOI: 10.3389/fphys.2020.00982
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Plasma Osteopontin and Arginine Pathway Metabolites in Patients With Overt Coronary Artery Disease

Abstract: Introduction Osteopontin (OPN) is involved in ectopic calcification. Its circulating form is upregulated in coronary artery disease (CAD) patients. Circulating OPN levels positively correlate with oxidative stress, one of the major triggers of endothelial dysfunction. Endothelial dysfunction is, in turn, associated with reduced nitric oxide (NO) bioavailability due to the impaired arginine pathway. The aim of this study was to better understand the correlations between OPN, oxidative stress marker… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 37 publications
0
1
0
Order By: Relevance
“…The association between OPN and impaired nitric oxide (NO) bioavailability could play a role in the inhibition of endothelial NO synthase in coronary artery disease patients [ 31 ]. Serum OPN identifies progression of coronary artery calcium scanning in patients without known atherosclerotic cardiovascular disease at baseline after 4-year follow-up [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…The association between OPN and impaired nitric oxide (NO) bioavailability could play a role in the inhibition of endothelial NO synthase in coronary artery disease patients [ 31 ]. Serum OPN identifies progression of coronary artery calcium scanning in patients without known atherosclerotic cardiovascular disease at baseline after 4-year follow-up [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that the impairment of endothelial function reflects the early stage of atherosclerosis, where OPN could be harmful. OPN is related to decreased activity of NO synthase (NOS) within atherosclerotic lesions, contributing to endothelial dysfunction in patients with coronary artery disease (CAD) [30]. Another study demonstrated that an OPN deficiency attenuates angiotensin II-induced aortic aneurysm and atherosclerosis in animal models [31].…”
Section: Factors Regulating the Atherogenetic Action Of Opnmentioning
confidence: 99%